How to Motivate Millennial Knowledge Workers of China in Financial Industry by Using Monetary and Non-monetary Rewards. - YANG, Di (2020)
Nowadays, millennial employees are pouring into the workplace, which brings great challenges to the management of enterprises. Besides, as the retirement rate of older generations continues to increase, the influence of millennials in China is becoming increasingly significant. In addition, with the arrival of the knowledge economy era, knowledge workers have become one of the most important sources for a company to succeed in fierce competition and long-term development. Especially in knowledge-intensive sectors such as the financial industry, the demand for knowledge workers is increasing in recent years. Therefore, it is crucial to examine the effective motivational drivers of millennial knowledge workers in China in order to attract and retain them.